Paradigm lost? A historical review of the application of systems theory to public relations since 1975. (September 2019) - Hiscock, Robert
This study traces the formative application of systems theory to public relations and its consideration as a promising paradigm framework for the field, through a rich array of critical perspectives, and more recent analyses that examine public relations as a social phenomenon. The principles of grounded theory are applied to the selection and assessment of a representative sample of academic literature published between 1975 and 2016. A categorization framework emerges from the thematic analysis of the data that re-evaluates the historical application of systems theory. Two main insights emerge from the study. First, even in cases where a specific systems theory is not directly invoked, systems concepts are evident throughout the data of this period. Second, although systems theory has been applied extensively in the analyses of the organization, and more lately in the analyses of the impacts of public relations on the social world as a whole, analysis of the individual as a system actor as a central unit of analysis was not apparent in the data. Accordingly, a reflection on the individual as a system actor is undertaken, along with an updated visual model of the public relations system. Concluding remarks summarize the case for the ongoing relevance of systems theory to public relations research, practice, and education.